Mitogen-Activated Protein Kinase Pathway in Amyotrophic Lateral Sclerosis - TG Sahana; Ke Zhang (Biomedicines, 2021)
Amyotrophic lateral sclerosis is a fatal motor neuron degenerative disease. Multiple genetic and non-genetic risk factors are associated with disease pathogenesis, and several cellular processes, including protein homeostasis, RNA metabolism, vesicle transport, etc., are severely impaired in ALS conditions. Despite the heterogeneity of the disease manifestation and progression, ALS patients show protein aggregates in the motor cortex and spinal cord tissue, which is believed to be at least partially caused by aberrant phase separation and the formation of persistent stress granules. Consistent with this notion, many studies have implicated cellular stress, such as ER stress, DNA damage, oxidative stress, and growth factor depletion, in ALS conditions. The mitogen-activated protein kinase (MAPK) pathway is a fundamental mitogen/stress-activated signal transduction pathway that regulates cell proliferation, differentiation, survival, and death. Here we summarize the fundamental role of MAPK in physiology and ALS pathogenesis. We also discuss pharmacological inhibitors targeting this pathway tested in pre-clinical models, suggesting their role as potential drug candidates.